Three-dimensional in vitro modeling of malignant bone disease recapitulates experimentally accessible mechanisms of osteoinhibition. Issue 12 (December 2018) - McNeill, Eoin; Reese, Robert; Tondon, Abishek; Clough, Bret; Pan, Simin; Froese, Jeremiah; Palmer, Daniel; Krause, Ulf; Loeb, David; Kaunas, Roland; Gregory, Carl
Abstract Malignant bone disease (MBD) occurs when tumors establish in bone, causing catastrophic tissue damage as a result of accelerated bone destruction and inhibition of repair. The resultant so-called osteolytic lesions (OL) take the form of tumor-filled cavities in bone that cause pain, fractures, and associated morbidity. Furthermore, the OL microenvironment can support survival of tumor cells and resistance to chemotherapy. Therefore, a deeper understanding of OL formation and MBD progression is imperative for the development of future therapeutic strategies. Herein, we describe a novel in vitro platform to study bone–tumor interactions based on three-dimensional co-culture of osteogenically enhanced human mesenchymal stem cells (OEhMSCs) in a rotating wall vessel bioreactor (RWV) while attached to micro-carrier beads coated with extracellular matrix (ECM) composed of factors found in anabolic bone tissue. Osteoinhibition was recapitulated in this model by co-culturing the OEhMSCs with a bone–tumor cell line (MOSJ-Dkk1) that secretes the canonical Wnt (cWnt) inhibitor Dkk-1, a tumor-borne osteoinhibitory factor widely associated with several forms of MBD, or intact tumor fragments from Dkk-1 positive patient-derived xenografts (PDX). Using the model, we observed that depending on the conditions of growth, tumor cells can biochemically inhibit osteogenesis by disrupting cWnt activity in OEhMSCs, while simultaneously co-engrafting with OEhMSCs, displacing them from the niche, perturbing their activity, and promoting cell death. In the absence of detectable co-engraftment with OEhMSCs, Dkk-1 positive PDX fragments had the capacity to enhance OEhMSC proliferation while inhibiting their osteogenic differentiation. The model described has the capacity to provide new and quantifiable insights into the multiple pathological mechanisms of MBD that are not readily measured using monolayer culture or animal models.